Nursing Academic Staff and Students in Oman's Level of Knowledge about Climate Change Issues and their Level of Compliance to The Go Green, Be Climate Positive Campaign - Valdez, Glenn Ford D; Al Amri, Salma; Al Mamari, Wadha; Kazmi, Hassan Abbas; Doloolat, Zakia; Mathew, Simy; Al Zuwameri, Noor; Javier, Maria Luisa; Jo, Zaida (Al-Hijrah Indonesia, 2024)
Higher education institution students, faculty, and staff give environmental awareness and green initiatives high emphasis for several reasons: promoting environmental awareness: Students are the future leaders of the planet and will oversee addressing climate change issues. Students’ environmental sensitivity is necessary for the advancement of a sustainable future, and college initiatives like “go green” and climate change awareness make this feasible. The study is a descriptive correlational study that aims to explore the student and faculty’s level of awareness regarding climate change and the level of compliance with the Go Green Be Climate Positive Campaign. The study population comprised of nursing students and nursing faculty members from Oman College of Health Sciences-Dhofar. The sample was obtained using consecutive sampling with a response turnover of 75%. The researchers devised an online questionnaire consisting of three parts which were tested for reliability and validity. The study utilized SPSS Version 25 to run descriptive and inferential tests. Result showed the majority of the respondents were females, singles, students who are Omanis and living in a rural setting within the dominant age range of 20-25. Level of awareness above the mean average of 3.50 and the level of compliance the mean average of 2.30. The study demonstrates that age and awareness levels are associated, and that compliance levels are related to awareness levels.